Teaching quality: The satisfaction of university students with their professors - Ruiz Esteban, Cecilia María; Santos del Cerro, Jesús (Anales de Psicología / Annals of Psychology, 2020)
For almost a century now, the concern of universities about student satisfaction with teaching quality has been increasing. A literature review has enabled the attributes of quality teaching to be classified into three main types: pedagogical, generic, and disciplinary. The aim of this paper is to identify the variables that, in the opinion of students, most influence student satisfaction regarding teaching quality. A total of 476 undergraduate students participated from Business Administration and Management of the University of Castilla-La Mancha (Spain). An ad hoc questionnaire was used to assess student satisfaction with teaching. Parametric (Logistic Regression Analysis) and non-parametric (Decision Tree) models were used. Our data indicate that if the professor explains the subject clearly, is concerned to find out whether the explanations have been understood, and carefully prepares the classes; the teaching-quality assessment will be very satisfactory. The identification of the attributes of quality teaching will enable universities to draw up initial and ongoing training plans for their teaching staff, bearing in mind the crucial role played by generic, pedagogical, and disciplinary competences in professor-student interaction.